Disease surveillance and farmers’ knowledge of Brachiaria (Syn. Urochloa) grass diseases in Rwanda - Uzayisenga, Bellancile; Mutimura, Mupenzi; Muthomi, J.W.; Mwang’ombe, A.W.; Ghimire, Sita R. (National Inquiry Services Center, 2021)
Brachiaria (syn. Urochloa) is one of the most important tropical forages grass of African origin. Its performance is affected by different constraints, including diseases. This study assessed the distribution, incidence and severity of Brachiaria diseases and documented farmers’ knowledge on Brachiaria diseases in Rwanda. Surveys were conducted in five districts in the dry and wet seasons of 2018 and 2019. Fungi associated with major diseases were isolated and identified based on internal transcribed spacer sequences. The demographic information and farmers’ knowledge of Brachiaria diseases and yield loss were collected using structured questionnaire. Surveys revealed widespread distribution of leaf blight, leaf rust and leaf spot diseases in Rwanda. Incidence and severity of these diseases differed significantly by districts, seasons and district × season interactions; the exception was the non-significant effect of season and district × season interactions on rust incidence in 2018. Molecular identification revealed Phakopsora apoda as a provisional leaf rust pathogen, and frequent association of fungi Epicoccum spp. and Nigrospora spp. with leaf blight, and Bipolaris secalis and Fusarium spp. with leaf spot symptoms. This study provides baseline information for future studies on Brachiaria diseases and recognises diseases as a major challenge to sustainable production of Brachiaria grass in Rwanda and East Africa.